Factors affecting the distribution of two Synechococcus ecotypes in the coastal Adriatic Sea - Šantić, Danijela; Šolić, Mladen; Marin, Ivana; Vrdoljak Tomaš, Ana; Kušpilić, Grozdan; Ninčević Gladan, Živana (2018)
Distribution and abundance of two Synechococcus ecotypes, phycocyanin-rich cells (PC-SYN) and phycoerythrin-rich cells (PE-SYN) were studied in the surface layer of the central Adriatic Sea during the 2015-2016 period. The studied area included several estuarine areas and coastal to open sea trophic gradients, covering a wide range of seawater temperatures \((11.82 - 20.75 oC)\), salinity (4.47 - 38.84) and nutrient concentration. The abundance of PC-SYN ranged from \( 0 to 79.79 x 10 3 cell mL -1\) and that of PE-SYN from \(5.01 x 10 3 to 76.74 x 10 3 cell mL -1\). Both ecotypes coexisted in the studied waters with PC-SYN cells dominating during spring and PE-SYN during winter and autumn. PC-SYN showed a significant positive relationship with temperature and strong positive responses to nitrogen nutrients, whereas PE-SYN positively responded to phosphate availability. The relative ratio of phosphorus availability and total inorganic nitrogen nutrients (N/P ratio) affects the spatial distribution of the two Synechococcus ecotypes.
U radu je istražena raspodjela i brojnost dva ekotipa roda Synechococcus, tzv. stanice bogate fikocijaninom (PC-SYN) i stanice bogate fikoeritrinom (PE-SYN) u površinskom sloju vodenog stupca, tijekom 2015. i 2016. godine. Područje istraživanja obuhvaćalo je nekoliko estuarijskih područja te područje trofičkog gradijenta od obale prema otvorenom moru, širokog raspona temperature mora \((11.82 - 20.75 oC)\), saliniteta (4.47-38.84) i koncentracije hranjiva. Brojnost PC-SYN bila je u rasponu od \( 0 to 79.79 x 10 3 cell mL -1\), a PE-SYN od \(5.01 x 10 3 to 76.74 x 10 3 cell mL -1\). Utvrđeno je istovremeno obitavanje oba ekotipa na istraživanom području, s prevladavanjem PC-SYN tijekom proljeća te PE-SYN tijekom zime i jeseni. Pokazana je statistički značajna povezanost između PC-SYN i temperature te njegova jaka pozitivna povezanost s dušikovim spojevima, dok su PE-SYN stanice pozitivno odgovorile na dostupnost fosfata. Relativni omjer dostupnosti fosfora i ukupnih hranjiva dušika (N/P omjer) utjecao je na prostornu raspodjelu oba ekotipa roda Synechococcus.
Bibliografija: str. 57-59.
Summary ; Sažetak.
Keywords: Fikoeritrinom -- Dušik -- Fosfor -- Synechococcus -- Trofičko stanje -- Ekološki čimbenici; Jadransko more